Calibration of exit velocity and temperature distribution for subsonic jet flow - Gan, Rui Zheng (2009)
Tabs have been known for a long time to have the capability to eliminate screech noise from supersonic jets. It is this application that has provided the most motivation for the subsequent studies on the effects of tabs have on jets. This Final Year Project is aimed to reproduce and calibrate the air flowing out of the exhaust of a jet engine, and to assist in the study of effects made by tabs to the jet stream at the nozzle exit. The rig was designed and constructed to mimic the airflow of a jet engine [1]. This rig was designed and made to produce airflow with speed of 100m/s and at temperature of 150 °C. The rig was subsequently put on trials with its results collected and analysed. The desired velocity and temperature distribution profiles of the rig should be uniform and symmetrical about the centre of the nozzle’s exit. The rig was found to be capable of producing a uniform velocity distribution profile. However, the temperature profile produced was found to be non‐uniform. The rig’s temperature profile was collected and examined to provide data for subsequent modifications to achieve the desired uniform temperature and velocity distribution profiles. Subsequently a set of delta and air tabs are fabricated and attached to the rig’s nozzle. These air tabs will be used to alter the temperature and velocity distribution profiles of the jet. Delta tabs were experimented and it is found that the delta tabs with orientation of φ ≈ 135° made a more pronounced deformation to the jet stream by bifurcating it. These results will be used as controlled variable for future studies of the air tabs.